Análise semiótica do texto jurídico - Magri, Wallace Ricardo (Estudos Semióticos, 2005)
The present work aims to analyze a judicial sentence based on the studies co-ordinated by A. J. Greimas in his book Sémiotique et sciences sociales,which will be the starting point for our own analysis.